Unilateral Withdrawal of the Fiduciary Security Object Without Any Default by the Debtor (Case Study of Decision No.36/Pdt.G.S/2023/PN Pdg) - Maharani, Marsya Arviela; Sulastri, Sulastri (Journal of Law, Politic and Humanities, 2025)
The development of Indonesia's financing sector has led to legal issues concerning fiduciary security, particularly the unilateral withdrawal of fiduciary collateral by creditors without any default by the debtor, as seen in Decision Number 36/Pdt.G.S/2023/PN Pdg. This research aims to analyze the legal protection for debtors and the liability of creditors when withdrawing fiduciary objects unilaterally in the absence of debtor default. The study employs a normative-juridical method with legislative and case-based approaches. Data was collected through literature review and analyzed qualitatively. The findings indicate that legal protection for debtors remains suboptimal due to the imbalance of power between creditors and debtors under Article 15(2) and (3) of Law No. 42/1999 on Fiduciary Security before the Constitutional Court’s ruling. However, Constitutional Court Decision No. 18/PUU-XVII/2019 strengthened the debtor's position by affirming that default and fiduciary execution must follow judicial procedures. Meanwhile, a creditor’s unilateral withdrawal of fiduciary collateral constitutes an unlawful act under Article 1365 of the Indonesian Civil Code, obliging the creditor to return the fiduciary object and compensate the debtor for material and immaterial losses. In conclusion, a legal balance between creditors and debtors is necessary to ensure fairness and legal certainty in the execution of fiduciary security